(untitled) (New York, 1995)
The book is divided into four parts. Part I intoduces the basic concepts and dxperimental methodologies of molecular cell biology. Part II teaches how genes work. Part III concentrates on the ways in which proteins work together to make a living cell. Part IV emphasizes the interactions of cells with each other, both in normal and abnormal situations
Keywords: Cytology,Molecular biology